Additional intermittent peritoneal dialysis in difficult-to-treat hemodialysis patients with severe heart disease - Dragan Klarić; Marta Klarić; Jagoda Nikić; Nikola Zagorec (Bulletin de la Dialyse à Domicile)
Usually, patients treated by peritoneal dialysis are switched to full-time hemodialysis due to technique failure. Sometimes, hemodialysis can be added to peritoneal dialysis to improve dialysis delivery. It can be difficult to use hemodialysis on patients with significant heart disease (valvular disease or ischemic cardiomyopathy) and severe heart failure due to common immediate complications and intradialytic hypotension that may worsen cardiac function, thus closing the vicious cycle of cardiac dysfunction and ischemia. This can result in poor dialysis delivery along with volume overload despite regular hemodialysis sessions. Here, we describe a case series of difficult-to-treat hemodialysis patients (7 males aged 51–73) with significant cardiac comorbidities and heart failure in whom additional intermittent peritoneal dialysis was reintroduced on top of regular hemodialysis. They all were initially treated by peritoneal dialysis (median duration of peritoneal dialysis treatment was 16 months, range 2–44) and then switched to full-time hemodialysis due to insufficient ultrafiltration or reasons unrelated to ultrafiltration, but thereafter, they faced significant hemodialysis-related complications and volume overload despite regular weekly sessions. Peritoneal dialysis (one manual exchange) was reintroduced (2–4 months after switching to full-time HD) on 3 hemodialysis-free days, and patients were followed up. After 12 months, better volume management (regression of pleural effusion, a reduction in water body mass composition (median of 1 vs. 2.4 L), reduced serum NT-proBNP values (median of 13,030 vs. 45,384 pg/ml)), better cardiac functional status, and a reduction in the frequency and number of dialytic complications were achieved. Moreover, during the 12-month follow-up, such bimodal treatment resulted in improved health-related quality of life as assessed by the WHOQoL-BREF questionnaire (median of 74 vs 55). The addition of peritoneal dialysis in difficult-to-treat hemodialysis patients may result in benefits despite additional costs and burdens for patients.